Analisis Usaha Mikro, Kecil, dan Menengah (UMKM) , Sistem Usaha Tani, dan Sistem Pemasaran Talas di Desa Situgede - Ahmad Yuda Pratama; Ninuk Purnaningsih (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Talas as one of the superior commodities of Bogor City can be utilized more widely not only sold in the market (retailer), but can be used as one of the diversified commodities, and is useful as other processed raw materials such as cakes, taro chips, lunkhead taro, taro flour and lying down. Obtained from more users Many taro plants in Situgede have created Micro, Small and Medium Enterprises (MSMEs) that are engaged in taro-based processed products that develop in the village of Situgede. Making empowerment and development of MSMEs becomes a thing that needs to be done in a sustainable manner. The production of taro in the city of Bogor is still fluctuating, this is needed by production factors (capital, labor, land, and management). In taro marketing activities, farmers often do not respond to the prices they receive (too low) while prices at the high end consumer level. The purpose of discussing this report is to identify the problems of MSMEs, channel taro farming systems, and marketing systems for taro in Situgede Village. This report uses a qualitative descriptive method using primary and secondary data. The methods used were observation, interviews, and observations through direct participation in the Situgede village community through the 2019 SLP SUIJI activities. Keywords: farming, marketing, MSMEs SUIJI SLP, taro